Active shooter live exercise: an important diagnose tool - M. Fernandes, Luís; Assis, Hugo; Mendes, João; Faria, Ricardo (Scientific Letters, 2024)
Background: Active-threat incidents are increasingly frequent, even within the European Union (EU). Multi-casualty incidents (MCI) are occurring in previously unaffected locations, amplifying the challenge for law enforcement and emergency services readiness. Violence in confined spaces, notably educational institutions, presents substantial security risks to public safety [1,2,3]. A common factor among active shooter scenarios is the selection of densely populated public venues. The Guarda Nacional Republicana (GNR) possesses territorial policing authority covering approximately 95% of the national territory, including the IUCS-CESPU Campus. Objective: The main objective of this study was to identify challenges faced by various institutions in responding to active threat situations with casualties on an Academic Campus. An integrated response is crucial for saving lives during active threat events. Coordinating law enforcement, emergency medical services, and academia necessitates joint training to optimise survival rates and mitigate post-event consequences. Methods: A simulation assessed the performance of an integrated Rescue Task Force (RTF), comprising the first Police Patrol, the Intervention Unit, and an INEM Special Team, in response to an active shooter incident. The simulation replicated a tactical incident, an MCI scenario of an active shooter on the IUCS-CESPU Campus. Multiple GNR teams, including Patrol and Intervention Units, were deployed to identify, search, and neutralise the threat. An emergency service team also participated in the final simulation. Results: Internal evaluations confirmed that all operators met the minimum mission standards. The average mission duration was 10 minutes. Conclusions: While completion of the simulation was not a definitive indicator of operational readiness, participant perception of its effectiveness as a training platform significantly improved post-exercise.